2015
DOI: 10.5966/sctm.2014-0215
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic Neural Stem/Progenitor Cells Derived From Embryonic Stem Cells Promote Functional Recovery After Transplantation Into Injured Spinal Cord of Nonhuman Primates

Abstract: Previous studies have demonstrated that neural stem/progenitor cells (NS/PCs) promote functional recovery in rodent animal models of spinal cord injury (SCI). Because distinct differences exist in the neuroanatomy and immunological responses between rodents and primates, it is critical to determine the effectiveness and safety of allografted embryonic stem cell (ESC)-derived NS/PCs (ESC-NS/PCs) in a nonhuman primate SCI model. In the present study, common marmoset ESC-NS/PCs were grafted into the lesion epicen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 66 publications
0
47
0
Order By: Relevance
“…When implanted into sites of spinal cord injury (SCI), rat-and human-derived multipotent neural progenitor cells, human embryonic stem cell-derived (ESC-derived) NSCs, and human induced pluripotent stem cell-derived (iPSC-derived) NSCs all extend very large numbers of axons over long distances and form synapses with host neurons (4,5) that in some cases support functional improvement (4,(8)(9)(10). These findings suggest the potential for human translation; indeed, NSC clinical trials for SCI have begun, and more are planned (ClinicalTrials.gov).…”
Section: Introductionmentioning
confidence: 99%
“…When implanted into sites of spinal cord injury (SCI), rat-and human-derived multipotent neural progenitor cells, human embryonic stem cell-derived (ESC-derived) NSCs, and human induced pluripotent stem cell-derived (iPSC-derived) NSCs all extend very large numbers of axons over long distances and form synapses with host neurons (4,5) that in some cases support functional improvement (4,(8)(9)(10). These findings suggest the potential for human translation; indeed, NSC clinical trials for SCI have begun, and more are planned (ClinicalTrials.gov).…”
Section: Introductionmentioning
confidence: 99%
“…To decide the time window of cell transplantation therapy for primates at subacute phase, we transplanted NPCs derived from common marmoset embryonic stem cells 14 days after SCI in a marmoset model, and demonstrated that the injected cells preferentially differentiated into neurons and oligodendrocytes, promoted neuronal interaction and myelination, and contributed to motor functional recovery (Iwai et al . ). These results suggest that NPC transplantation is effective in a primate model of SCI, lending more support to the feasibility of delayed injection of human NPCs in human SCI.…”
Section: Application Of Human Npcs For Scimentioning
confidence: 97%
“…; Iwai et al . ). Therefore, it is suitable to establish a cell bank and stock hiPSC‐NPCs in order to provide cells for use in allogenic transplantation (Okano and Yamanaka ).…”
Section: For Clinical Application Of Human Ipsc‐npcsmentioning
confidence: 97%
“…On the other hand, essential elements of cell sources must be considered to develop the cell/tissue replacement and promote the outcome efficiency. First they must be allogeneic to reduce the unwanted immune-responses 37 , further they should represent higher surviving rate to promote the clinical applications 38 . Also the cell sources must be able to be prepared by standard methods to control the expression of undesired phenotype and risk of dyskinesia 39 .…”
Section: Stem Cells and Tissue Engineeringmentioning
confidence: 99%
“…The discovery of the unique properties of these stem cells, their self-renewing ability, and their responsiveness to particular stimulations by undergoing differentiation to different specific cell types, paved the way for a revolution in regenerative medicine 41 . For example Iwai et al 37 , demonstrated that ESC obtained from allogeneic sources could be used to generate neurons and to from synaptic connections in a non-human primate. Kassmer et al 42 reported new type of PSCs known as very small embryonic-like cells that have potential ability to generate all cell types including the neurons.…”
Section: Stem Cells and Tissue Engineeringmentioning
confidence: 99%